Spatio-temporal variability in underwater light climate in a turbid river-floodplain system. Driving factors and estimation using Secchi disc - Mayora, Gisela Paola (2019)
The underwater light climate has important effects on primary producers. The aim of this research was to evaluate its variability in a turbid river-floodplain system. Photosynthetically active radiation (PAR) was measured in the Middle Paraná River during different hydrological phases to (a) analyse the photosynthetically active radiation attenuation coefficient (k) and euphotic depth (Zeu) as well as their associations with optically active components and (b) develop and evaluate indices and regression models based on Secchi disc (SD) measurements to estimate k and Zeu. Values of k were higher in the fluvial system than in the floodplain and during low-water stage than high-water stage. Particulate components controlled the light climate variability. Chromophoric dissolved organic matter and chlorophyll-a had significant effects during floods. The estimation of k and Zeu was sensitive to temporal but not to spatial variations. The highest prediction accuracy was observed when using specific non-linear regressions for each hydrological phase, especially for Zeu estimation (low stage: k = 1.76 × SD−0.80, Zeu = 2.62 × 1/SD−0.80; high stage: k = 2.04 × SD−0.53, Zeu = 2.26 × 1/SD−0.53). The indices k × SD and Zeu/SD were significantly different from those proposed for clear water environments. It is concluded that temporal variations should be considered when estimating k and Zeu in turbid river-floodplain systems because of the temporal heterogeneity in optically active components. Considering that ecological implication of the light climate depends on Zeu:depth ratio, we propose to estimate Zeu instead of k. Finally, indices proposed for clear water environments are not recommended to be applied to turbid environments.